Janus Pt surfaces derivatized with zwitterionic molecules for oxygen reduction reactions in alkaline and acid electrolytes - Jung, Namgee; Shin, Hyeyoung; Kim, Mansu; Jang, Injoon; Kim, Hyoung-Juhn; Jang, Jong Hyun; Kim, Hyungjun; Yoo, Sung Jong (ELSEVIER SCIENCE BV, 2015)
Direct electrostatic interactions between a charged Pt surface and oppositely charged spectator ions are utilized for the enhancement of oxygen reduction reaction (ORR) activity in both KOH and H3PO4 solutions. Zwitterionic L-cysteine molecules functionalized on a Pt surface are turned outwards to afford differing surface charges in either alkaline (-) or acid solutions (+). In KOH solution, this leads to the selective impediment of interactions between OH- and K+ with the Pt surface through repulsive and attractive interactions of the negatively charged -COO- group of L-cysteine, respectively. In H3PO4 solution, the phosphoric acid molecule and its anion are effectively captured by the positively charged -NH3+ moieties of L-cysteine. Behaviors of the spectator species hindering the ORR are systematically controlled through direct electrostatic interactions with the functional groups of L-cysteine in each electrolyte, resulting in a Janus Pt catalyst for superior ORR in both alkaline and acid electrolytes. (C) 2015 Elsevier Ltd. All rights reserved.